AGRI-INDUSTRIAL SITUATIONER: BASIS FOR STRATEGIC PLANS - Arceño, Rose A; Prieto, Amela Lourdes M (PEOPLE: International Journal of Social Sciences, 2019)
In the Regional Development Plan (RDP) of Region VIII, Philippines, the centerpiece is along agri-industrial development. This study primarily aimed to delve into the patterns and trends of the agri-industrial development of Palompon, Leyte, Philippines, covering the period of 1999-2009, with the variables as geopolitical profile with 4 indicators, economic profile with 7 indicators, and socio-demographic aspect with 8 indicators. This study adopted a descriptive-evaluative research design using 3 levels of growth diagnostic approach to facilitate description and analysis of the patterns and trends of the favorable and unfavorable development in the locality. Analysis of development patterns and trends utilized a time-series method and a factor analysis to determine the factors associated with agri-development variables. Findings depict of a 2nd class municipality with a land area of 12,846 hectares in 50 villages) with 22% residing in urban villages and 88% residing in rural villages. The indicators under the economic profile showed an improving mode through the years, while the indicators under the socio-demographic profile are in an increasing trend over the years. Thus, the municipality’s identified strengths are enhanced, and its weaknesses are developed and given attention to, for a progressive municipality of Palompon in the 4th district of Leyte.